Isolation of a heterotrophic nitrification-aerobic denitrification strain and identification of its potential electricity generation ability in microbial fuel cells. Issue 1 (2nd January 2023) - Song, Siru; Zhang, Mingchuan; Xu, Xinyang
ABSTRACT: To construct a simultaneous nitrification and denitrification-microbial fuel cell (SND-MFC) reactor for stable electricity generation, a heterotrophic nitrification-aerobic denitrification strain was isolated and purified from aerobic activated sludge from a sewage treatment plant. The strain with an optimal nitrogen removal performance, which was identified as Pseudomonas, was inoculated into the SND-MFC as a single strain. Different electrode materials and electrode distances (EDs) were investigated. The results showed that a maximum ammonium removal rate of 92.31% and a maximum power density of 134.28 mW/m 3 were obtained by the SND-MFC using graphene film as the electrodes material. Decreasing the ED did not significantly improved the power generation performance of the pure strain SND-MFC at the initial stage. When the electrode distance of the SND-MFC was 4 cm, the best generation efficiency was achieved with a maximum power density of 151.84 mW/m 3 . GRAPHICAL ABSTRACT: UF0001